Nivel de satisfacción de los pacientes frente a la calidad de atención de salud recibida en el Hospital Manuel Ygnacio Monteros vs Hospital Isidro Ayora de la ciudad de Loja periodo febrero-juio 2016 - Quizhpe Carrillo, Gabriela Jasmín (2017)
The assistance quality in health services and the degree of satisfaction of their patients are the mainstay in the progress of any health institution, the present study is a descriptive and transversal research, whose objectives were; identify the level of satisfaction of patients against the quality of health assistance; establish satisfaction or dissatisfaction of patients against the objective and subjective quality according to the score SERVQHOS in “Manuel Ygnacio Monteros” Hospital and “Isidro Ayora” Hospital in Loja city. The universe consisted in 239 external users, 120 of them belong to “Isidro Ayora” Hospital and 119 to “Manuel Ygnacio Monteros” Hospital (IESS). The information was collected through the application of surveys using the SERVQHOS questionnaire (Cronbach alpha of 0.96), which measured the following levels of satisfaction: satisfied, very satisfied, not satisfied at all and slight satisfied, obtaining the following results, in “Manuel Ygnacio Monteros” Hospital 51% of external users were satisfied; while 54% of “ Isidro Ayora” Hospital stated they were satisfied with the care received, in relation to the objective and subjective component had an average of 3.92 and 3.69 in “Isidro Ayora” Hospital; respectively; Unlike “Manuel Ygnacio Monteros” Hospital where objective quality had an average of 3.88 and the subjective of 3.67, in conclusion there is a moderate percentage of satisfaction in the users that go to these two establishments. Key words: assistance quality, satisfaction level, SERVQHOS.